2020
DOI: 10.1371/journal.pone.0231269
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the applicability and utility of a gamified didactics with exergames at primary schools: Qualitative findings from a natural experiment

Abstract: One of the main objectives of Physical Education in elementary schools is to encourage motivation so that the subject enhances academic performance and the practice of physical exercise. Didactic research should evaluate the effectiveness of educational methods to know if they are applicable, useful, and in what sense. Exergames are digital motor games that aim to stimulate players' motor skills. Gamification refers to the use of game-based elements in nongame contexts to motivate actions. This research evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(60 citation statements)
references
References 54 publications
0
34
0
4
Order By: Relevance
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…After the four phases of selecting the eligible articles for review, 45 were found to be suitable to be used in this systematic review due to the nature of the respective studies. From the articles, four main aspects of teachers' perspectives on the use of Quizizz could be seen, mainly, effectiveness , feasibility [14,15,19,20,22,23,26,27,31,36,38,41,[43][44][45][46][47][48], difficulty [16,17,19,26,28,31,39,41,43,46,[48][49][50][51][52], and motivation [14,17,[24][25][26]31,32,35,38,40,41,44,45,47,49,50,…”
Section: Resultsmentioning
confidence: 99%
“…This made up 40% of what teachers also considered when deciding whether or not to use Quizizz in their teaching and learning sessions. Quintas-Hijos et al [44] stated that teachers consider Quizizz quite feasible because using it is convenient for all users. However, they still need to be connected to the Internet in order to participate in the sessions.…”
Section: Teachers' Perspective On the Feasibility Of Quizizzmentioning
confidence: 99%
See 2 more Smart Citations
“…Quantitative descriptive analyses were previously performed with the obtained data (see Table 2). This information was used as an indicator to direct the thematic analysis, similarly to one of our previous studies [46]. More specific descriptive analyses are found in the Supplementary Material (S3: Classification tree, coding sheets).…”
Section: Resultsmentioning
confidence: 99%